Odontogenic Fascial Space Infection in Diabetic and Non-Diabetic Patients: A Clinical Comparative Study - Yadav, Deepak; Mishra, Ravish; Kandel, Laxmi; Ali, Shahid (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Maxillofascial space infections are commonly encountered conditions and its prevalence is more in South Asia compared to other regions due to lack of awareness in seeking dental treatment. Carious teeth, contiguous non-vital teeth, postoperative infections, periodontal disease and pericoronal infections are major sources of odontogenic infections. These infections can easily spreads into facial spaces which may lead into life threatening conditions. Facial space infections with comorbid conditions of patients always increases extent of severity. Among the various systemic comorbidities, diabetes is commonly associated with space infections, which determines over all prognosis and treatment. The present study aims to ﬁnd out the prevalence of diabetes, demographic value, the odontogenic spaces involved, educational value in relation, and the inﬂuence of systemic comorbidity over the treatment. MATERIAL AND METHODS This descriptive cross-sectional study was conducted at the Department of Oral and Maxillofacial Surgery at Universal College of Medical Sciences (UCMS), Bhairahawa from November 2023 to October 2024. All the patients were enrolled in this study after proper counselling and informed written consent. Diabetic and non-diabetic patients were considered as group A and group B respectively. Demographic data and prevalence of maxillofascial infection, role of education, facial spaces involved were the variables of this study. RESULTS The total number of cases during the study period were 3441. Out of which 56 were diagnosed with maxillofacial space infections and only 40 met the inclusion criteria of the study. The prevalence during this period was (16.27 per thousand). The study comprised 40 patients with maxillofascial space infections, divided into two groups based on their medical history and lab investigations. Out of which, 25 patients were diabetic (Group A) and 15 were non-diabetic (Group B). CONCLUSION This study found a higher prevalence of maxillofascial space infections in diabetic patients, with female predilection. The mean age group affected was 49.88 years and submandibular space infections was the most common among all.